Reconstructing Entrepreneurship Learning Through a Managerial Approach Based on Local Ethnoscience - Azzajjad, Muhammad Fath; Ahmar, Dewi Satria; Ningsih, Purnama; Nurfianti (Quantitative Economics and Management Studies, 2025)
This study looks at how students' abilities in contextual company development are affected when entrepreneurship education is reconstructed using a management style grounded on local ethnoscience. 18 students from the 2019 cohort who took the Entrepreneurship course in the Chemistry Education programme at Universitas Sembilanbelas November Kolaka provided survey data for the study. Through direct observation and group business planning, students were introduced to fundamental entrepreneurial principles and assisted in interacting with local ethnoscientific resources, including sago, cassava, green vegetables (spinach), clove, honey, shrimp, and milkfish. Standardised questionnaire encompassing eight important markers of ethnoscientific understanding in entrepreneurship was used to gather data. To understand the findings, descriptive and mapping data analysis were used. The findings show that students are highly engaged and competent in locating, evaluating, and innovatively using local resources for entrepreneurship. The most motivating resources were honey, cassava, and shrimp, and students showed great aptitude in contextual business design, product creation, and team-based entrepreneurial analysis. The main results support the idea that including local ethnoscience into entrepreneurship education increases both practical entrepreneurial abilities and cultural and ecological sensitivity. This concept is a potential educational framework for creating entrepreneurs who are innovative, locally rooted, and prepared for the future.